2017
DOI: 10.1002/jsfa.8361
|View full text |Cite
|
Sign up to set email alerts
|

Can sesame consumption improve blood pressure? A systematic review and meta‐analysis of controlled trials

Abstract: Hypertension is a major risk factor for cardiovascular disease, myocardial infarction, stroke and renal failure. Sesame consumption may benefit blood pressure (BP) owing to its high polyunsaturated fatty acid, fibre, phytosterol and lignan contents. To clarify this, a systematic review and meta-analysis of controlled trials was conducted. The PubMed (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Cochrane Library (Central) databases were systematically searched until August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Among food sources of isoflavones, a meta-analysis exploring the effects of soybeans on blood pressure in postmenopausal women showed that ingestion of ≥25 g soy protein per day had blood pressure-lowering effects, and the improvements in blood pressure may be due to the isoflavones component of soy protein [57]. Other sources of phytoestrogens are seeds, which are rich in lignans: meta-analyses on clinical trials evaluating the effects of flaxseeds and sesame consumption on blood pressure concluded that they both may exert blood pressure-lowering effects [58,59]. Among the major sources of phenolic acids, the most comprehensive meta-analysis of cohort studies on coffee consumption and incidence of new-onset hypertension reported a modest decrease in risk of hypertension [60], while several meta-analyses investigating the effects of tea on blood pressure, showing potential benefits for long-term (>12 weeks) intake [61,62] and significant effects also for secondary prevention of cardiovascular disease among overweight and obese adults [63] and in individuals within pre-hypertensive and hypertensive ranges [64].…”
Section: Discussionmentioning
confidence: 99%
“…Among food sources of isoflavones, a meta-analysis exploring the effects of soybeans on blood pressure in postmenopausal women showed that ingestion of ≥25 g soy protein per day had blood pressure-lowering effects, and the improvements in blood pressure may be due to the isoflavones component of soy protein [57]. Other sources of phytoestrogens are seeds, which are rich in lignans: meta-analyses on clinical trials evaluating the effects of flaxseeds and sesame consumption on blood pressure concluded that they both may exert blood pressure-lowering effects [58,59]. Among the major sources of phenolic acids, the most comprehensive meta-analysis of cohort studies on coffee consumption and incidence of new-onset hypertension reported a modest decrease in risk of hypertension [60], while several meta-analyses investigating the effects of tea on blood pressure, showing potential benefits for long-term (>12 weeks) intake [61,62] and significant effects also for secondary prevention of cardiovascular disease among overweight and obese adults [63] and in individuals within pre-hypertensive and hypertensive ranges [64].…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin (see Fig 6 ), which exists in the oil of sesame seeds and some other plants, was one of the major components, as shown in Table 1 . It exhibits a variety of biological activities, such as lipid-lowering [ 13 ], antihypertensive [ 14 ], antioxidant [ 15 ], and anticancer effects. [ 16 ] In regard to its antitumor effects, Sesamin has already been confirmed to be active against several cancer cell types, including prostate cancer, breast cancer, colon cancer, and human lung cancer[ 17 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, meta-analyses of randomized controlled trials on soy supplementation showed a significant reduction in BP, despite results were not univocal: indeed, subgroup analyses showed more consistent evidence when considering hypertensive, but not normotensive individuals [ 15 ] with no dose-response relationship [ 16 ]. Meta-analyses of randomized controlled trials on lignan-rich foods, such as sesame [ 17 ], black cumin [ 18 ], and flaxseed [ 19 ], have provided evidence of a significant effect in reducing BP. Nevertheless, some randomized-controlled trials showed null or scanty significant results [ 20 ].…”
Section: Discussionmentioning
confidence: 99%